Longitudinal spinal cord atrophy in multiple sclerosis using the generalized boundary shift integral - Moccia, Marcello; Prados, Ferran; Filippi, Massimo; Rocca, Maria A.; Valsasina, Paola; Brownlee, Wallace J.; Zecca, Chiara; Gallo, Antonio; Rovira, Alex; Gass, Achim; Palace, Jacqueline; Lukas, Carsten; et al. (Annals of neurology, 2019)
Objective Spinal cord atrophy is a clinically relevant feature of multiple sclerosis (MS), but longitudinal assessments on magnetic resonance imaging using segmentation‐based methods suffer from measurement variability, especially in multicenter studies. We compared the generalized boundary shift integral (GBSI), a registration‐based method, with a standard segmentation‐based method. Methods Baseline and 1‐year spinal cord 3‐dimensional T1‐weighted images (1mm isotropic) were obtained from 282 patients (52 clinically isolated syndrome [CIS], 196 relapsing–remitting MS [RRMS], 34 progressive MS [PMS]), and 82 controls from 8 MAGNIMS (Magnetic Resonance Imaging in Multiple Sclerosis) sites on multimanufacturer and multi–field‐strength scans. Spinal Cord Toolbox was used for C2‐5 segmentation and cross‐sectional area (CSA) calculation. After cord straightening and registration, GBSI measured atrophy based on the probabilistic boundary‐shift region of interest. CSA and GBSI percentage annual volume change was calculated. Results GBSI provided similar rates of atrophy, but reduced measurement variability compared to CSA in all MS subtypes (CIS: −0.95 ± 2.11% vs −1.19 ± 3.67%; RRMS: −1.74 ± 2.57% vs −1.74 ± 4.02%; PMS: −2.29 ± 2.40% vs −1.29 ± 3.20%) and healthy controls (0.02 ± 2.39% vs −0.56 ± 3.77%). GBSI performed better than CSA in differentiating healthy controls from CIS (area under the curve [AUC] = 0.66 vs 0.53; p = 0.03), RRMS (AUC = 0.73 vs 0.59; p < 0.001), PMS (AUC = 0.77 vs 0.53; p < 0.001), and patients with disability progression from patients without progression (AUC = 0.59 vs 0.50; p = 0.04). Sample size to detect 60% treatment effect on spinal cord atrophy over 1 year was lower for GBSI than CSA (CIS: 106 vs 830; RRMS: 95 vs 335; PMS: 44 vs 215; power = 80%; alpha = 5%). Interpretation The registration‐based method (GBSI) allowed better separation between MS patients and healthy controls and improved statistical power, when compared with a conventional segmentation‐based method (CSA), although it is still far from perfect. ANN NEUROL 2019 ANN NEUROL 2019;86:704–713